FACTORS INFLUENCING CAPITAL ADEQUACY IN BUSINESS ORGANIZATIONS: A CASE OF KENYA'S INSURANCE INDUSTRY - Jane, Lewis Wanja; Ayako, Dr. Aloys B.; Kinai, Mr. William (International Journal of Finance, 2017)
Abstract Purpose: The purpose of this study was to determine the factors influencing capital adequacy in business organizations. Methodology: A case study design was. The study consisted of 46 insurance companies. The data is quantitative and secondary data collection method was used. The study used descriptive and regression approach in data analysis. Using Statistical Package for Social Sciences (SPSS) regression analysis model was calculated. Data was presented in tables and graphs. Results: Regression analysis showed that ownership listing status had a beta coefficient of (-16.614) and that it was statistically insignificant (0.329). Regression analysis showed that dividend payout ratio had a beta coefficient of -0.455 and that it was statistically significant (0.000). Regression analysis showed that the profitability ratio had a beta coefficient of 0.485 and that it was statistically significant (0.000). Regression analysis showed that the liquidity ratio had a beta coefficient of 0.226 and that it was statistically significant (0.000). Regression analysis showed that the cost of capital had a beta coefficient of -0.566 and that it was statistically insignificant (0.125). Unique contribution to theory, practice and policy: The study recommended that insurance Regulatory Authority should put in measures to make the insurance companies adhere to the recent regulations and policies which require the companies to have minimum capital requirements and hence in turn increasing capital adequacy.